Consumer Rights in the Case of Pertamax Adulteration - Dita Kartika Sari Hasibuan; Poppy Wulandari (International Forum of Researchers and Lecturers, 2025)
This research discusses consumer rights in the case of Pertamax adulteration by PT Pertamina Patra Niaga, which involved mixing fuel with substances of lower quality than promised. This case not only economically harms consumers but also endangers user safety and undermines public trust in the products sold by the state-owned company. The research methodology employed is normative legal research with a descriptive-analytical approach, examining the legal aspects related to consumer rights violations and the effectiveness of the implementation of the Consumer Protection Law in resolving disputes. The findings indicate that weak supervision and law enforcement allowed the adulteration practices to occur. Therefore, this research suggests the need for improved oversight by the government and BPH Migas, stricter law enforcement, and consumer education to protect their rights. It is hoped that this research will contribute to the development of consumer protection in Indonesia.